Empirical investigation of a Stochastic model based on intensity values for terrestrial laser scanning - Lambertus, T.; Belton, David; Helmholz, Petra (2018)
Stochastic information of measurements has always been an important part in the field of geodesy. Especially for engineering tasks like deformation monitoring the knowledge of achieved precision is of vital importance. For more than a decade terrestrial laser scanners have been used for high precise measurement applications, however there has been a lack of focus in the literature of an adequate stochastic model for terrestrial laser scanning. This contribution presents a comprehensive empirical experiment containing numerous laser scans at various scan configurations in order to examine a stochastic model based on intensity values. The results confirm the fundamental suitability of intensity values for a stochastic modelling but also point out certain problems concerning scanning geometry. High incidence angles in laser scanning can lead to an improvement of the precision in object's surface normal direction, which agrees with a previously proposed theoretical model for positional uncertainty of laser scan 3D points and should not be ignored in further development of a stochastic model based on intensity values. Based on these results a stochastic model was estimated and the precision of 3D points explicitly expressed as function of intensity and incidence angle.